محددات إجراء فحص لطاخة عنق الرحم لدى السيدات المراجعات لمشفى تشرين الجامعي - عيسى, مروان (Latakia University Journal -Medical Sciences Series, 2017)
يعد السرطان بشكل عام المسبب الثاني للوفاة بعد أمراض القلب والأوعية في البلدان المتقدمة ويعد سرطان عنق الرحم ثاني أكثر أنواع السرطان شيوعاً عند النساء في البلدان المتقدمة والنامية , ويعتبر الكشف المبكر عن سرطان عنق الرحم عاملا مهما جداً في زيادة معدل الشفاء ومعدل البقيا ، ومن أهم طرقه فحص لطاخة عنق الرحم لاكتشاف التغيرات غير الطبيعية في أنسجة عنق الرحم والموصى بأجرائه كل ثلاث سنوات للنساء في سن النشاط الجنسي ويعتبر إجراء سهل وغير مكلف وغير مؤلم وحساسيته عالية ويساهم في إنقاص أعباء العلاج و التقليل من معدل الوفيات والامراضيات. و وفقا للعديد من الدراسات هناك محددات تحول دون إجرائه منها نقص المعلومات عن الإجراء , صعوبة الوصول الى المشفي, الألم, التكلفة , الآثار الجانبية ,الشعور بالخجل و الإحراج من الإجراء, عدم التشجيع من قبل الفريق الصحي او الزوج , عدم الشعور بأية أعراض تدفعها لإجراء الفحص والخوف من اكتشاف السرطان لديهن ومن هنا تأتي أهمية هذه الدراسة لمعرفة المعوقات التي تحد من إجراء فحص اللطاخة في مجتمعنا السوري و اقتراح الحلول المناسبة , إضافة إلى أنه لم تجر أية دراسة بهذا الخصوص في سوريا اجري البحث على عينة قوامها 100 سيدة متزوجة من مشفى تشرين الجامعي في اللاذقية بطريقة الاعتيان الملائم وقد أظهرت النتائج أن غالبية أفراد العينة (80%) لم يقمن بإجراء فحص اللطاخة, وأن (93,75%) منهن لم يقمن بإجراء فحص اللطاخة كان بسبب عدم وجود مشكلة نسائية لديهن ,وكان السبب في (75%)من الحالات أنهن يخشين من اكتشاف السرطان و (85%) منهن يشعرن بالخجل و الإحراج من إجرائه و (12.5%) عدم وجود الوقت الكافي للإجراء و (62.5%) منهن يعتقدن بان الإجراء مؤلم , بينما كان السبب في (90%) من الحالات كان عدم التشجيع من الأطباء و الممرضين و نسبة (87.5%) كان السبب لديهن هو نقص المعلومات حول الإجراء, لذلك اقترحت الدراسة تصميم و تنفيذ برامج تثقيفية حول أهمية و فوائد و طريقة فحص لطاخة عنق الرحم. Cancer is generally causing a second death after heart and blood vessels in the developed countries diseases is cervical cancer, the second most common cancer among women in developed and developing countries and is considered the early detection of cervical cancer is a very important factor in the increase cure rate and the rate of survival, and the most important ways screening Pap smear to detect abnormal changes in cervical tissue and recommended to initiate it every three years for women in the age of sexual activity and is an easy and inexpensive and painless, and high sensitivity and contributes to reducing the burden treatment and reduce the deaths and morbidity rate., according to several studies there are many obstacles that prevent it, including the lack of information,, difficulty of access to hospitals, pain, cost, side effects, feeling of shame and embarrassment of procedure, lack of encouragement by the health team, or the husband, not feeling any symptoms paid to conduct the examination, and the fear of discovery of the cancer . the importance of this study was to find out the obstacles that limit the conduct smear screening in the Syrian society and propose appropriate solutions in addition to that not conducted any study in this area in Syria this research was conducted on a sample of 100 married woman of tishreen University Hospital in Latakia in manner convenient sampling. The results showed that the majority of respondents (80%) did not undergo the smear examination, and that the majority of the respondents (93.75%) who did not undergo the smear examination was due to the lack of women's problem to have, and it was the reason (75%) of cases they fear the cancer is detected and 85% of them feel ashamed and embarrassed of the vote and (12.5%) do not have the time to conduct and (62.5 %) they believe that the procedure is painless and (90%) was the lack of encouragement from the doctors and nurses and the proportion (87.5%) was the lack of information about the procedure,Therefore proposed design and implementation of educational programs about the importance , benefits and methode of screening